Theoretical Principles of Sociology, Volume 2 Microdynamics - Turner, Jonathan H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Micro-level dynamics revolve around face-to-face interactions among individuals. What occurs within encounters is constrained by their embedding with corporate and categoric units and, by extension, institutional domains, stratification systems, community networks, societies, and inter-societal systems. In this Handbook, the author explores the effect of microdynamics on these larger social systems.
The Micro-level Realm of Social Reality -- The Embedding of Encounters -- Ecological and Demographic Dynamics in Encounters -- Status Dynamics in Encounters -- Role Dynamics in Encounters -- Cultural Dynamics in Encounters -- Motivational Dynamics in Encounters -- Emotional Dynamics in Encounters -- The Micro Basis of the Meso and Macro Social Realms -- Principles of Microdynamics.
Keywords: Social sciences; Social Sciences; Sociology, general